The identity of the third generation in the novel Himmelskörper written by Tanja Dückers - Chodorowska, Natalia (Acta Universitatis Lodziensis. Folia Germanica, 2018)
The object of the article is the novel Himmelskörper written by Tanja Dückers, the representative of the third post-war generation. The discourse in the family communication and memory space, the relation to family members from the experience generation, as well as the trips in the home towns of the forefathers in the former eastern territories of Germany turn out as important fields of the search for the post-war generation’s identity. The question is asked how memories of the Second World War and the post-war period are constructed in the family context, how the representatives of the third generation deal with the family’s past. In addition, the role of the return to the home towns of the grandparents and parents for the descendants and whether these journeys lead to the constitution of the feeling of self is analysed.